Urethral Meatus and Glanular Closure Line: Normal Biometrics and Clinical Significance - Abbas, Tariq O.; Ali, Mansour (Urology Journal, 2018)
Purpose: The aim of this study is to explore the normal external urethral meatal and glans closure line in normal boys, and to investigate the correlation between these glans biometrics and the age of the participants. Material and Method: 103 male children were asked to participate in the study during ritual circumcision. Parents of 94 of them (mean age 5.9 years, range 0.6–13) accepted while remaining 9 did not. Glans biometrics were measured using digital calipers. Result: 100% of the study participants had a vertical slit-like meatal opening located at the tip of the glans. The length of the meatal opening was 5.3 (± 1) mm and of ventral glans closure was 4.8 (±1.1) mm. Significant correlation between both the external meatal opening and closure lines lengths and age was observed. Moreover, the meatal opening size was correlated to the glans closure line as well (r = 0.36, confidence interval 0.14–0.54, P < .001). Conclusion: The site and size of the meatus opening in normal male children is consistent, and ventral glans closure is equal to or slightly less than meatal length. These findings could aid in glanular reconstruction configuration during hypospadias surgery.